2022
DOI: 10.3389/fcell.2022.852752
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Neuroinflammation Associated With Neurodevelopmental Disorders: A Microglial Perspective

Abstract: Neuroinflammation is a cause of neurodevelopmental disorders such as autism spectrum disorders, fetal alcohol syndrome, and cerebral palsy. Converging lines of evidence from basic and clinical sciences suggest that dysregulation of the epigenetic landscape, including DNA methylation and miRNA expression, is associated with neuroinflammation. Genetic and environmental factors can affect the interaction between epigenetics and neuroinflammation, which may cause neurodevelopmental disorders. In this minireview, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 141 publications
(190 reference statements)
1
9
0
Order By: Relevance
“…Moreover, the expression of MMP9 is elevated in several neurological conditions, including ischemia, neurodegenerative diseases (e.g., Parkinson’s, Huntington’s, and Alzheimer’s diseases), ASDs, Fragile X syndrome [ 32 , 49 , 64 , 65 ], and in neuroinflammatory disorders such as multiple sclerosis, for which MMP9 has been proposed to have a pathogenetic role in the disruption of the BBB [ 49 ]. This scenario allows to hypothesize that the enhanced expression of Mmp9 in the cortex, cerebellum and hippocampus of Mecp2 -null mice might be indicative of a neuroinflammatory state caused by a BBB breakdown, in line with the evidence of neuroinflammation reported in RTT [ 51 , 52 ]. Studies performed in superoxide dismutase (SOD)1-null mice suggested that oxidative stress might play a role in the alteration of BBB permeability, possibly through the stimulation of MMP9 [ 65 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Moreover, the expression of MMP9 is elevated in several neurological conditions, including ischemia, neurodegenerative diseases (e.g., Parkinson’s, Huntington’s, and Alzheimer’s diseases), ASDs, Fragile X syndrome [ 32 , 49 , 64 , 65 ], and in neuroinflammatory disorders such as multiple sclerosis, for which MMP9 has been proposed to have a pathogenetic role in the disruption of the BBB [ 49 ]. This scenario allows to hypothesize that the enhanced expression of Mmp9 in the cortex, cerebellum and hippocampus of Mecp2 -null mice might be indicative of a neuroinflammatory state caused by a BBB breakdown, in line with the evidence of neuroinflammation reported in RTT [ 51 , 52 ]. Studies performed in superoxide dismutase (SOD)1-null mice suggested that oxidative stress might play a role in the alteration of BBB permeability, possibly through the stimulation of MMP9 [ 65 ].…”
Section: Discussionsupporting
confidence: 58%
“…Matrix Metallopeptidase 9 ( Mmp9 ) is a metalloproteinase known to impact BBB permeability by inducing the degradation of basal lamina and TJs, as well as to stimulate the release of cytokines and free radicals, thus contributing to enhance neuroinflammation [ 49 , 50 ], previously advocated as a possible mechanism for developmental cognitive impairment also in RTT syndrome [ 51 , 52 ]. In order to understand whether Mmp9 may play a role in the BBB perturbation in RTT mice, the expression of its transcript in symptomatic Mecp2 -/y mice was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Among the most static positions, some psi sites are found on genes linked to neuronal functions: SLC2A1 is associated with GLUT1 deficiency syndrome, a neurological disorder characterized by seizures, developmental delay, and movement disorders 75 . Dysregulation of UHRF1 has been implicated in various cancers and neurodevelopmental disorders 76,77 . EIF4EBP2 regulates translation initiation by binding to eukaryotic translation initiation factor 4E (eIF4E) and inhibiting its interaction with the mRNA cap structure.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond infectious or post-infectious inflammatory disorders, ongoing developments in the literature emphasize the role of inflammation in normal and abnormal brain development. Although the question of neuroinflammatory factors in autism spectrum disorder has long been considered, including recent discussion of the relationships between autism and autoimmune encephalitis, considerations across different neurodevelopmental disorders have been expanding, potentially mediated by DNA methylation and miRNA expression due to inflammatorily driven epigenetic factors [52,53].…”
Section: Neurodevelopmental Conditions and Neuroinflammationmentioning
confidence: 99%
“…For example, although immunological defects have long been reported in individuals with 22q11.2 deletion syndrome, a strong association between markers of autoimmunity and neuropsychiatric disorders was recently described [57]. Ongoing developments include consideration of neuroinflammatory factors in features of individuals with foetal alcohol syndrome, cerebral palsy and other neurodevelopmental disorders [58,53].…”
Section: Andandmentioning
confidence: 99%